Ekspor CPO (Crude Palm Oil) Indonesia Ke India Dengan Analisis Model Gravity - Siti Abir Wulandari (Universitas Batangahari Jambi, 2022)
The agricultural sector is one of the sectors that takes a role in international trade. Exports are one way to increase state revenues and in turn can stimulate an increase in Gross Domestic Product (GDP). Exports are the most important part that must be considered for the achievement of sustainable economic development. In this case the progress of the export of a country that has no constraints will benefit the country itself. One of Indonesia's mainstay export commodities is palm oil (CPO). India is the main destination country for Indonesian CPO exports. The consumption of vegetable oils in India has increased over the past two decades as populations grow, incomes increase, and restaurants have sprung up to cater to crowds who start eating out more often. The Indian state's vegetable oil imports have soared to 15 million tonnes from 4 million just two decades ago, but imports fell in 2019/20 and 2020/21 after pandemic-related lockdowns that swept the world. The study aims to describe Indonesia's palm oil exports to India and to determine the factors affecting Indonesia's palm oil exports to India. This research was conducted in the destination country of Indonesia's palm oil (CPO) export to India, with the data collection time from 1992 to 2020. The palm oil commodity in this study is based on the harmonized system (HS) 151190010 published by the United Nations Commission trade (UN Comtrade). The method used in this study is time series analysis using a gravity model approach. The results of the analysis using the gravity method show that GDP per capita in Indonesia is based on constant prices, GDP per capita in India is based on constant prices, Indian tariffs and economic distance have a significant effect on the value of Indonesia's CPO exports to India.